Mortality and risk of cardiac complications among immediate survivors of accidental electric shock: a Danish nationwide cohort study - Christian Torp-Pedersen; Sam Riahi; Lars Køber; Steen Møller Hansen; Peter Søgaard; Rikke Mortensen; Søren Hjortshøj (BMJ Open)
Objective Exposure to electric shock has been associated with an increased risk of developing delayed cardiac arrhythmias and cardiac diseases. We examined whether electric shock patients have an increased risk of developing cardiac disease, cardiac arrhythmias or death compared with the general Danish population.Design Matched cohort study.Setting A nationwide study in Denmark from 1994 to 2011.Participants We identified 11 462 Danish patients who visited an emergency ward or were admitted to a hospital due to electric shock from 1994 to 2011. Each patient was matched for age and sex with five random controls from the Danish population.Main outcome measures Mortality, cardiac procedures and cardiac diseases following electric shock.Results A total of 7390 electric shock patients were seen at an emergency ward and 4072 electric shock patients were admitted to a hospital. The median patient age was 28.6 years (Q1–Q3, 21.3–37.7) for the emergency ward patients and 26.4 years (Q1–Q3, 18.3–37.4) for admitted patients. In both groups, most patients were male (74.0% and 76.8%). Few of the electric shock patients had a record of cardiovascular disease at baseline (364/11 462, 3.2%). The 5-year cumulative incidence of death was 0.47% (95% CI 0.29% to 0.65%) for emergency ward patients and 1.04% (95% CI 0.71% to 1.37%) for admitted patients. No difference in 5-year survival was observed compared with matched controls (emergency ward, p=0.10; admitted patients, p=0.80). Fewer than four patients received a pacemaker within 30 days.Conclusions This nationwide study did not demonstrate an increase in mortality among patients seen at hospitals after accidental electric shock compared with a background population. Cardiac procedures and diseases following electric shock were very rare. We suggest that nearly all patients can be discharged safely from the emergency room after electric shock without further observation.